Mengkoordinir Ragam Format Acara Dakwah - Erwan Effendy; Muhammad Arif Hafizd Lubis; Ahmad Maulana; Juni Ariansyah Pulungan (Journal on Education, 2023)
The term program can be analogous to goods (goods) or services (services) that are sold to other forms of business. Programs or often referred to as events are items that people need so they are willing to listen to them. In the world of radio, understanding the station format is the heart of all programming performance. Every broadcast program production process refers to the choice of radio station format which is increasingly specific (segmented) as the number of radio stations increases and listeners become more segmented. The more modern the radio, the more specialized the format, the more competitive a radio is, the more focused its program position will be. The sharpening of broadcast programs is a consequence of the sharpness of broadcast formats. The event itself means: “activities that are shown, broadcast, or contested; programs (television, radio, etc.)